A high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, a preparation method and applications thereof

CN123033852APending Publication Date: 2026-11-03SHAANXI IND VOCATIONAL & TECH COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611338907.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies for preparing high-Fe-content iron-based amorphous nanocrystalline soft magnetic alloys suffer from poor amorphous formation ability and limited cooling rate, resulting in coarse and unevenly distributed α-Fe grains and deterioration of coercivity, making it difficult to achieve synergistic optimization of high saturation magnetic induction intensity and low coercivity.

Method used

By using composition design and liquid nitrogen-assisted cooling rapid cooling and spin-coating method, α-Fe crystal nuclei with a size of less than 10 nm are uniformly precipitated in situ in an amorphous matrix under quenched conditions. Combined with extreme cooling conditions, abnormal grain growth is suppressed, and a uniform and fine nanocrystalline/amorphous dual-phase structure can be prepared in one step.

Benefits of technology

With an Fe content ≥ 83 at.%, the alloy strip exhibits high saturation magnetic induction intensity Bs ≥ 1.75T and low coercivity Hc ≤ 15A/m. It has a large tolerance for process parameters, is suitable for industrial production, and reduces raw material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033852A_ABST
    Figure CN123033852A_ABST
Patent Text Reader

Abstract

The application discloses a high-Fe soft-magnetic amorphous nanocrystalline alloy ribbon and a preparation method and application thereof, and belongs to the technical field of Fe-based amorphous nanocrystalline soft-magnetic alloy materials. a Si b B c P d C e ) 100‑f Cu f and inevitable impurities, wherein 0.83 <= a <= 0.86, 0.01 <= b <= 0.03, 0.08 <= c <= 0.11, 0.02 <= d <= 0.04, 0.01 <= e <= 0.02, 0.5 <= f <= 1, and a+b+c+d+e=1; the alloy ribbon uniformly in-situ precipitates alpha-Fe crystal nuclei with a size of less than 10 nm in an amorphous matrix in a quenched state. The alloy ribbon has a saturation magnetic induction intensity Bs >= 1.75 T and a coercive force Hc <= 15 A / m, realizes the synergistic optimization of high Bs and low Hc, and can be applied to high-frequency transformers, new-energy automobile driving motors, inductance elements, magnetic sensors or electromagnetic shielding devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of iron-based amorphous nanocrystalline soft magnetic alloy materials, specifically relating to a high-Fe soft magnetic amorphous nanocrystalline alloy thin strip, its preparation method, and its application. Background Technology

[0002] Iron-based amorphous and nanocrystalline soft magnetic alloys, possessing both high saturation magnetic induction and low coercivity, have become core magnetic materials in power electronics fields such as high-frequency transformers, drive motors for new energy vehicles, inductive components, magnetic sensors, and electromagnetic shielding devices. Increasing the Fe content is the key way to improve the alloy's saturation magnetic induction, but increasing the Fe content will drastically weaken the alloy's amorphous forming ability, leading to uncontrolled crystallization during rapid quenching.

[0003] Currently, the mainstream preparation process for iron-based amorphous and nanocrystalline soft magnetic alloys is a two-step method: first, a completely amorphous precursor strip is prepared by single-roll rapid quenching, and then annealing is performed to precipitate nanocrystals in the amorphous matrix, obtaining a nanocrystalline / amorphous dual-phase structure. Patent publication number CN116313356A discloses an iron-based amorphous-nanocrystalline soft magnetic alloy, its strip material, and its preparation method. The Fe content is 75-80 at.%, and Co 3-5 at.% is added. In the quenched state, it is a completely amorphous alloy strip (critical thickness ≥30μm). After annealing at 340℃-420℃ for 10 min, the saturation magnetic induction intensity is 1.67T-1.72T. Patent publication number CN120048609A discloses an iron-based amorphous nanocrystalline soft magnetic alloy material, its preparation method, and its application. The Fe content is 83.3 at.%, Si is 4%, B is 4%-8%, P is 4%, Cu is 0.7%, and C is 0-4%. In the quenched state, it is an amorphous ribbon. After one heat treatment (heating at 10℃ / min-40℃ / min to 370℃-550℃, holding for 30s-420s) or segmented heat treatment, the average size of α-Fe grains is 16 nm-27 nm, the saturation magnetic induction intensity is 1.57-1.85T, and the coercivity is 6.64A / m-26.26A / m.

[0004] However, the aforementioned existing technologies all rely on annealing crystallization (a two-step method) – the annealing process has a narrow window and is sensitive to temperature and time; high-Fe alloy amorphous precursors have poor thermal stability, and during annealing, α-Fe nucleation and growth rates are rapid, leading to grain coarsening, uneven distribution, and deterioration of coercivity. Specifically, CN116313356A limits the Fe content to below 80 at.% and relies on Co to improve magnetic properties, resulting in high raw material costs and limited improvement in saturation magnetic induction; although CN120048609A increases the Fe content to 83.3 at.%, the α-Fe grain size after annealing still reaches 16nm-27nm, with a coercivity upper limit as high as 26.26A / m. Slow-heating annealing is sensitive to temperature and time, making it difficult to simultaneously achieve high saturation magnetic induction and low coercivity.

[0005] In principle, if uniform and fine nanocrystals could be directly precipitated during rapid cooling and solidification, the annealing process could be eliminated, achieving a one-step preparation method. However, existing technologies generally do not employ a one-step method, with the core challenges being: firstly, high-Fe alloys have poor amorphous formation capabilities, and the cooling capacity of conventional single-roller rapid quenching is limited—the cooling rate is constrained by the thermal conductivity of the copper roller, the contact state between the melt and the roller surface, and the temperature rise of the roller surface. Insufficient cooling results in coarse-sized (up to 200 nm or more) and unevenly distributed α-Fe grains precipitated during solidification, leading to a sharp deterioration in coercivity; secondly, the one-step method requires the in-situ precipitation of high-density, uniform, and fine crystal nuclei during solidification while ensuring the formation of the amorphous matrix. The precipitation and growth of crystal nuclei are extremely sensitive to cooling conditions, and conventional cooling methods cannot simultaneously meet the dual requirements of "inhibiting grain coarsening" and "inducing uniform nucleation." Therefore, existing technologies can only employ a two-step method of "fully amorphous in quenched state + annealed crystallization," using the annealing process to separate and control the nucleation and growth processes to obtain a nanocrystalline / amorphous dual-phase structure. Summary of the Invention

[0006] To address the problems existing in the prior art, the present invention aims to provide a high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, its preparation method, and its application. The alloy ribbon uniformly precipitates α-Fe crystal nuclei with a size of less than 10 nm in situ in an amorphous matrix under quenched conditions. Abnormal grain growth is suppressed by quenched in-situ crystal nuclei regulation, thereby achieving synergistic optimization of high saturation magnetic induction intensity and low coercivity.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: The present invention provides a high-Fe soft magnetic amorphous nanocrystalline alloy thin strip, wherein the alloy thin strip is composed of (Fe a Si b B c P d C e ) 100-f Cu fThe alloy consists of unavoidable impurities, wherein the subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following conditions: 0.83≤a≤0.86, 0.01≤b≤0.03, 0.08≤c≤0.11, 0.02≤d≤0.04, 0.01≤e≤0.02, 0.5≤f≤1, and a+b+c+d+e=1; the alloy ribbon, in the quenched state, uniformly precipitates α-Fe crystal nuclei with a size of less than 10 nm in situ in the amorphous matrix.

[0008] Furthermore, the alloy strip is composed of (Fe) a Si 0.02 B c P 0.03 C 0.01 ) 99.5 Cu 0.5 It consists of unavoidable impurities, where 0.83≤a≤0.86, 0.08≤c≤0.11, and a+c=0.94.

[0009] Furthermore, the alloy strip has a saturation magnetic induction intensity Bs≥1.75T and a coercivity Hc≤15A / m.

[0010] The present invention also provides a method for preparing the above-mentioned alloy strip, comprising the following steps: preparing raw materials, based on (Fe a Si b B c P d C e ) 100-f Cu f The subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, with 0.83≤a≤0.86, 0.01≤b≤0.03, 0.08≤c≤0.11, 0.02≤d≤0.04, 0.01≤e≤0.02, and 0.5≤f≤1, and a+b+c+d+e=1. The raw materials are selected as either elemental or alloy; the raw materials are smelted; and the alloy strip is prepared using a rapid cooling and spinning method.

[0011] Furthermore, in the rapid cooling and spinning method, the copper roller rotation speed is 40m / s-55m / s, and the cooling rate is 10. 5 K / s-10 6 K / s, copper roller surface roughness is 0.1μm-0.15μm, and alloy melt layup thickness is 10μm-20μm.

[0012] Furthermore, liquid nitrogen is used for assisted cooling in the rapid cooling and spinning method, so that the surface temperature of the copper roller is -150°C to -196°C before the alloy melt comes into contact with the copper roller.

[0013] Furthermore, in the liquid nitrogen-assisted cooling, the liquid nitrogen injection flow rate is 0.5L / min-2.0L / min, and the distance between the liquid nitrogen nozzle and the surface of the copper roller is 0.2mm-1.0mm.

[0014] Furthermore, the melting is carried out under vacuum, and the temperature is maintained at a temperature 150°C-200°C higher than the melting point of the alloy for at least 10 minutes.

[0015] Furthermore, the distance between the nozzle of the smelting furnace and the surface of the copper roller is 1mm-2mm.

[0016] The present invention also provides the application of the above-mentioned alloy strip in high-frequency transformers, new energy vehicle drive motors, inductive components, magnetic sensors or electromagnetic shielding devices.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) In-situ crystal nucleus control in quenched state: In the quenched state, the alloy of the present invention uniformly precipitates α-Fe crystal nuclei with a size of less than 10 nm in the amorphous matrix. These crystal nuclei compete with the newly generated α-Fe grains for growth during subsequent solidification and heat treatment, effectively suppressing abnormal grain growth and obtaining a uniform and fine nanocrystalline / amorphous dual-phase structure. This solves the problem that high Fe content alloys are prone to precipitating coarse grains and deteriorating magnetic properties during rapid quenching.

[0019] (2) Synergistic effect of high Bs and low Hc: The alloy of the present invention still maintains excellent soft magnetic properties under the condition of Fe content ≥83at.%, with saturation magnetic induction intensity Bs≥1.75T and coercivity Hc≤15A / m (Bs reaches up to 1.9T and Hc reaches down to 4.3A / m in the examples), which is better than the performance obtained by the two-step annealing method in the prior art (Bs≤1.72T in CN116313356A and Hc upper limit of 26.26A / m in CN120048609A).

[0020] (3) Process-friendly and wide window: The extreme cooling conditions of the copper roller surface temperature of -196℃ to -150℃ before the alloy melt comes into contact with the copper roller are achieved by liquid nitrogen enhanced cooling. There is no need to rely on slow heating annealing. The process parameters have large tolerance and strong controllability, which is conducive to stable industrial production.

[0021] (4) Low cost: The alloy system does not contain expensive elements such as Co, Ni, Nb, and Zr, resulting in low raw material costs and suitability for large-scale production. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 TEM image of the soft magnetic amorphous nanocrystalline alloy thin strip prepared in Example 1 of this invention;

[0024] Figure 2 This is a SEM image of the soft magnetic amorphous nanocrystalline alloy thin strip prepared in Example 1 of the present invention;

[0025] Figure 3 This is a SEM image of the soft magnetic amorphous nanocrystalline alloy strip prepared in Comparative Example 1 of this invention. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the scope of protection of the present invention.

[0028] This invention addresses the problems of narrow process window and easy coarsening and uneven grains in the existing two-step process of "quenched fully amorphous + annealed crystallization" for high Fe content iron-based amorphous and nanocrystalline alloys. The invention proposes the following concept: By designing the composition, α-Fe crystal nuclei with a size of less than 10 nm are uniformly precipitated in situ in the amorphous matrix during the rapid cooling and spinning process (quenched state). With the help of liquid nitrogen-assisted cooling, extreme cooling conditions are achieved, so that the crystal nuclei obtain a high-density, uniform and fine precipitation state during the solidification stage. This suppresses abnormal grain growth without relying on traditional slow annealing, and obtains a uniform and fine nanocrystalline / amorphous dual-phase structure, achieving synergistic optimization of high saturation magnetic induction (Bs) and low coercivity (Hc).

[0029] To facilitate understanding of this invention, the terms involved in this invention are explained as follows:

[0030] (1) "Quenched state": refers to the state of the alloy melt after rapid cooling and solidification, without any subsequent heat treatment. In this invention, the alloy strip in the quenched state contains in-situ precipitated α-Fe crystal nuclei, rather than being completely amorphous;

[0031] (2) "In-situ precipitation": refers to the direct nucleation and precipitation of α-Fe crystal nuclei in the amorphous matrix during rapid cooling and solidification, rather than being induced by subsequent annealing. Under liquid nitrogen enhanced cooling conditions, the melt rapidly crosses the solidification zone, and Cu element acts as a nucleating element to promote the uniform nucleation of α-Fe phase at the solidification front.

[0032] (3) "Uniform": refers to the dispersed distribution and concentrated size of α-Fe crystal nuclei in the amorphous matrix, as confirmed by transmission electron microscopy (TEM); correspondingly, the quenched thin strip still shows an amorphous structure when detected by X-ray diffraction (XRD) (the crystal nucleus size is less than 10 nm and the volume fraction is low, so XRD cannot distinguish it), and the two are not contradictory;

[0033] (4) "Unavoidable impurities": refers to trace impurity elements that are unavoidably introduced during the raw materials or preparation process, whose content does not seriously affect the amorphous forming ability and soft magnetic properties of the alloy strip.

[0034] This invention provides a high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, wherein the alloy ribbon is composed of (Fe a Si b B c P d C e ) 100-f Cu fThe alloy consists of unavoidable impurities, wherein the subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following conditions: 0.83≤a≤0.86, 0.01≤b≤0.03, 0.08≤c≤0.11, 0.02≤d≤0.04, 0.01≤e≤0.02, 0.5≤f≤1, and a+b+c+d+e=1; the alloy ribbon, in the quenched state, uniformly precipitates α-Fe crystal nuclei with a size of less than 10 nm in situ in the amorphous matrix. Fe is the main magnetic element, and its content determines the theoretical upper limit of the alloy's saturation magnetic induction. This scheme limits the Fe content to 0.83≤a≤0.86, ensuring high Bs while avoiding a sharp decline in amorphous formation ability due to excessive Fe content. Si and B are metalloid elements that can significantly improve the alloy's amorphous formation ability. Among them, the B content (0.08≤c≤0.11) is key to maintaining the formation of the amorphous matrix. P and C are trace additives. P is enriched in the residual amorphous phase during α-Fe crystallization, stabilizing the amorphous phase and refining the grains. C can increase the difference in atomic radius, improve amorphous formation ability and thermal stability. Cu is a nucleation element that precipitates before α-Fe to form clusters during solidification, serving as nucleation sites for α-Fe, increasing the nucleation rate and refining the grains. Uniform in-situ precipitation of α-Fe nuclei with a size of less than 10 nm in the quenched state competes with the growth of newly formed α-Fe grains in the subsequent process, effectively inhibiting abnormal grain growth. Therefore, under the condition of Fe content ≥83 at.% in high-speed rail, it is still possible to achieve synergistic optimization of high Bs (≥1.75T) and low Hc (≤15A / m).

[0035] In a preferred embodiment, the alloy strip is made of (Fe) a Si 0.02 B c P 0.03 C 0.01 ) 99.5 Cu 0.5 The composition includes unavoidable impurities, where 0.83 ≤ a ≤ 0.86, 0.08 ≤ c ≤ 0.11, and a + c = 0.94. In this embodiment, Fe and B satisfy a linkage relationship a + c = 0.94, meaning that as the Fe content increases, the B content decreases accordingly. The trace elements Si, P, C, and Cu are fixed at preferred values, corresponding to the composition of the embodiment. Therefore, the uniformity of crystal nucleus precipitation and soft magnetic properties are further optimized, resulting in stable performance and good reproducibility.

[0036] The alloy strip has a saturation magnetic induction intensity Bs ≥ 1.75T and a coercivity Hc ≤ 15A / m. The alloy strip meets the requirements of high-frequency transformers, new energy vehicle drive motors, and other high-end devices for high magnetic induction intensity and low loss.

[0037] This invention provides a method for preparing the above-mentioned alloy strip, comprising: preparing raw materials based on (Fe a Si b B c P d C e ) 100-f Cu f The subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, with 0.83 ≤ a ≤ 0.86, 0.01 ≤ b ≤ 0.03, 0.08 ≤ c ≤ 0.11, 0.02 ≤ d ≤ 0.04, 0.01 ≤ e ≤ 0.02, and 0.5 ≤ f ≤ 1, and a + b + c + d + e = 1. Elemental or alloy raw materials are selected; the raw materials are smelted; and the alloy strip is prepared using a rapid cooling and spinning method. An alloy strip containing quenched in-situ crystal nuclei can be obtained in a single rapid cooling and spinning step, eliminating the need for the lengthy annealing process in the traditional two-step method, resulting in a simplified process, high efficiency, and low cost.

[0038] In the rapid cooling and spinning method, the copper roller rotation speed is 40m / s-55m / s, and the cooling rate is 10. 5 K / s-10 6 The parameters are K / s, copper roller surface roughness of 0.1μm-0.15μm, and alloy melt thickness of 10μm-20μm. These parameters work together to ensure stable formation of the amorphous matrix and uniform precipitation of α-Fe crystal nuclei. Among them, the surface roughness of the copper roller is crucial to the heat conduction of the rapid cooling process. When the surface roughness is too small (e.g., less than 0.1μm), the melt is difficult to form a continuous liquid film on the roller surface, and discontinuous spreading leads to uneven cooling. When the surface roughness is too large (e.g., greater than 0.15μm), the contact thermal resistance between the melt and the roller surface increases, the heat conduction efficiency decreases, and the cooling rate is insufficient. By controlling the roughness at 0.1μm-0.15μm, a balance between a continuous liquid film and efficient heat conduction can be achieved.

[0039] It should be noted that the alloy melt layup thickness is crucial, as this parameter affects the uniformity of α-Fe nucleus distribution and thermal conductivity in the prepared alloy ribbon. If the layup thickness is too thin, an amorphous matrix is ​​easily formed, requiring subsequent annealing. However, the annealing process window is small, and given that the Fe content in this embodiment is 0.83≤a≤0.86, controlling the annealing process is extremely difficult and cannot be applied in engineering. Conversely, if the layup thickness is too thick, the distribution of α-Fe nuclei in the thickness direction will be uneven. To achieve the aforementioned layup thickness, strict requirements are placed on the composition of the alloy melt. The alloy composition and superheat are the most important factors affecting the layup thickness. The alloy composition and superheat affect the viscosity of the alloy melt; higher viscosity results in a thicker layup, and lower viscosity results in a thinner layup. The composition and process provided by this invention can achieve an alloy melt layup thickness of 10μm-20μm.

[0040] The rapid cooling and spinning method employs liquid nitrogen-assisted cooling, ensuring that the surface temperature of the copper roller is between -150°C and -196°C before the alloy melt contacts the roller. This extreme low temperature pre-cools the melt before it contacts the roller, significantly increasing the supercooling at the solidification front, suppressing grain coarsening, and promoting high-density, uniform precipitation of crystal nuclei.

[0041] In the liquid nitrogen-assisted cooling process, the liquid nitrogen injection flow rate is 0.5 L / min to 2.0 L / min, and the distance between the liquid nitrogen nozzle and the surface of the copper roller is 0.2 mm to 1.0 mm. This allows for precise control of the liquid nitrogen cooling intensity and the distribution of the low-temperature zone, stabilizing the low-temperature environment and preventing liquid nitrogen splashing from interfering with the stability of the alloy liquid flow.

[0042] The melting process employs vacuum melting, involving holding at a temperature 150°C-200°C above the alloy's melting point for at least 10 minutes. The vacuum environment prevents oxidation of the melt and ensures the purity of the composition; holding at 150°C-200°C above the melting point allows for sufficient diffusion of alloying elements and uniform composition, laying the foundation for uniform crystal nuclei precipitation.

[0043] The distance between the nozzle of the melting furnace and the surface of the copper roller is 1mm-2mm. This ensures uniform spread of the melt, resulting in a thin alloy strip of uniform thickness and avoiding strip defects caused by unstable liquid flow.

[0044] This invention provides an application of a high-Fe soft magnetic amorphous nanocrystalline alloy strip, which is used in high-frequency transformers, drive motors for new energy vehicles, inductive components, magnetic sensors, or electromagnetic shielding devices. This fully leverages the advantages of high Bs and low Hc, contributing to the miniaturization, efficiency improvement, and energy saving of power electronics and new energy devices.

[0045] To further illustrate the present invention, the inventive points of the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0046] Example 1

[0047] This invention provides a high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, wherein the alloy ribbon is composed of (Fe a Si b B c P d C e ) 100-f Cu f It consists of unavoidable impurities, where the subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following conditions: a = 0.83, b = 0.02, c = 0.11, d = 0.03, e = 0.01, and f = 0.5.

[0048] The preparation method of the alloy strip in this embodiment includes the following steps:

[0049] Step 1: Raw material pretreatment and proportioning: Select Fe, Si, Cu and Fe-B, Fe-P and Fe-C master alloys with a purity ≥99.95% as raw materials, weigh them according to the above atomic proportions, remove the surface oxide layer by grinding, ultrasonically clean with anhydrous ethanol for 5 min, and preheat at 100℃ for 10 min.

[0050] Step 2, Vacuum melting: The proportioned raw materials are loaded into a crucible, vacuumed to below 5×10⁻³Pa, filled with high-purity argon, heated to a temperature 150°C higher than the alloy melting point, held for 10 minutes, and melted repeatedly 4 times to obtain a master alloy with uniform composition.

[0051] Step 3, Rapid Cooling and Roll Spinning: Crush the master alloy into 4g pieces and load them into a quartz tube with a 1mm diameter nozzle at the bottom. Adjust the distance between the furnace nozzle and the copper roller surface to 1mm. Start the liquid nitrogen-assisted cooling system, controlling the liquid nitrogen injection flow rate to 0.5L / min and the distance between the liquid nitrogen nozzle and the copper roller surface to 0.2mm, so that the surface temperature of the copper roller is -150℃ to -196℃ before the alloy melt contacts the copper roller. After remelting the master alloy, spray it onto the copper roller surface through the nozzle. The copper roller rotates at 40m / s, and the cooling rate is 10. 5 K / s-10 6 With a K / s ratio and a copper roller surface roughness of 0.1 μm, an alloy strip with an alloy melt layup thickness of 10 μm was obtained.

[0052] The obtained alloy ribbon was characterized as follows: Figure 1 As shown, it exhibits an amorphous structure in the quenched state; as Figure 2 As shown, observations revealed uniform in-situ precipitation of α-Fe nuclei with a size less than 10 nm in the amorphous matrix, exhibiting concentrated and uniform nuclei size distribution. This was confirmed by measuring the saturation magnetic induction intensity B. s The coercivity is 1.75 T, and the coercivity is H. c It is 4.3 A / m.

[0053] Example 2

[0054] This invention provides a high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, wherein the alloy ribbon is composed of (Fe a Si b B c P d C e ) 100-f Cu fThe alloy consists of unavoidable impurities, wherein the subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following conditions: a = 0.84, b = 0.02, c = 0.10, d = 0.03, e = 0.01, and f = 0.5; the alloy ribbon, in the quenched state, uniformly precipitates α-Fe crystal nuclei with a size of less than 10 nm in situ in the amorphous matrix.

[0055] The preparation method of the alloy strip in this embodiment includes the following steps:

[0056] Step 1: Raw material pretreatment and proportioning: Select Fe, Si, Cu and Fe-B, Fe-P and Fe-C master alloys with a purity ≥99.95% as raw materials, weigh them according to the above atomic proportions, remove the surface oxide layer by grinding, ultrasonically clean with anhydrous ethanol for 8 minutes, and preheat at 120℃ for 15 minutes.

[0057] Step 2, Vacuum melting: The proportioned raw materials are loaded into a crucible, vacuumed to below 5×10⁻³Pa, filled with high-purity argon, heated to a temperature 180℃ higher than the alloy melting point, held for 10 minutes, and melted repeatedly 3 times to obtain a master alloy with uniform composition.

[0058] Step 3, Rapid Cooling and Roll Spinning: Crush the master alloy into 5g pieces and load them into a quartz tube with a 1mm diameter nozzle at the bottom. Adjust the distance between the furnace nozzle and the copper roller surface to 1.5mm. Start the liquid nitrogen-assisted cooling system, controlling the liquid nitrogen injection flow rate to 1.0L / min and the distance between the liquid nitrogen nozzle and the copper roller surface to 0.5mm, so that the surface temperature of the copper roller is -150℃ to -196℃ before the alloy melt contacts the copper roller. After remelting the master alloy, spray it onto the copper roller surface through the nozzle. The copper roller rotates at 50m / s, and the cooling rate is 10. 5 K / s-10 6 With a K / s ratio and a copper roller surface roughness of 0.12 μm, an alloy strip with an alloy melt layup thickness of 15 μm was obtained.

[0059] The obtained alloy ribbon was characterized: XRD analysis in the quenched state showed an amorphous structure, and TEM observation revealed uniform in-situ precipitates of α-Fe nuclei smaller than 10 nm in the amorphous matrix, with concentrated and uniformly distributed nuclei. The saturation magnetic induction intensity B was measured. s The coercivity is 1.86 T, and the coercivity is H. c It is 6.6 A / m.

[0060] Example 3

[0061] This invention provides a high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, wherein the alloy ribbon is composed of (Fe a Si b B c Pd C e ) 100-f Cu f It consists of unavoidable impurities, where the subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following conditions: a = 0.85, b = 0.02, c = 0.09, d = 0.03, e = 0.01, and f = 0.5.

[0062] The preparation method of the alloy strip in this embodiment includes the following steps:

[0063] Step 1: Raw material pretreatment and proportioning: Select Fe, Si, Cu and Fe-B, Fe-P and Fe-C master alloys with a purity ≥99.95% as raw materials, weigh them according to the above atomic proportions, remove the surface oxide layer by grinding, ultrasonically clean with anhydrous ethanol for 10 min, and preheat at 150℃ for 20 min.

[0064] Step 2, Vacuum melting: The proportioned raw materials are loaded into a crucible, vacuumed to below 5×10⁻³Pa, filled with high-purity argon, heated to a temperature 200℃ higher than the alloy melting point, held for 10 minutes, and melted repeatedly 4 times to obtain a master alloy with uniform composition.

[0065] Step 3, Rapid Cooling and Roll Spinning: Crush the master alloy into 6g pieces and load them into a quartz tube with a 1mm diameter nozzle at the bottom. Adjust the distance between the furnace nozzle and the copper roller surface to 2mm. Start the liquid nitrogen-assisted cooling system, controlling the liquid nitrogen injection flow rate to 2.0L / min and the distance between the liquid nitrogen nozzle and the copper roller surface to 1.0mm, so that the surface temperature of the copper roller is -150℃ to -196℃ before the alloy melt contacts the copper roller. After remelting the master alloy, spray it onto the copper roller surface through the nozzle. The copper roller rotates at 55m / s, and the cooling rate is 10. 5 K / s-10 6 With a K / s ratio and a copper roller surface roughness of 0.15 μm, an alloy strip with an alloy melt layup thickness of 20 μm was obtained.

[0066] The obtained alloy ribbon was characterized: XRD analysis in the quenched state showed an amorphous structure, and TEM observation revealed uniform in-situ precipitates of α-Fe nuclei smaller than 10 nm in the amorphous matrix, with concentrated and uniformly distributed nuclei. The saturation magnetic induction intensity B was measured. s The coercivity is 1.88T, and the coercivity H is... c It is 6.7 A / m.

[0067] Example 4

[0068] This invention provides a high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, wherein the alloy ribbon is composed of (Fe a Si b Bc P d C e ) 100-f Cu f It consists of unavoidable impurities, where the subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following conditions: a = 0.83, b = 0.03, c = 0.08, d = 0.04, e = 0.02, and f = 1.

[0069] The preparation method of the alloy strip in this embodiment is the same as that in Example 1.

[0070] The obtained alloy ribbon was characterized: XRD analysis in the quenched state showed an amorphous structure, and TEM observation revealed uniform in-situ precipitates of α-Fe nuclei smaller than 10 nm in the amorphous matrix, with concentrated and uniformly distributed nuclei. The saturation magnetic induction intensity B was measured. s The coercivity is 1.90 T, and the coercivity is H. c It is 7.1 A / m.

[0071] Example 5

[0072] This invention provides a high-Fe soft magnetic amorphous nanocrystalline alloy ribbon, wherein the alloy ribbon is composed of (Fe a Si b B c P d C e ) 100-f Cu f It consists of unavoidable impurities, where the subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following conditions: a = 0.86, b = 0.02, c = 0.08, d = 0.03, e = 0.01, and f = 0.5.

[0073] The preparation method of the alloy strip in this embodiment is the same as that in Example 2.

[0074] The obtained alloy ribbon was characterized: XRD analysis in the quenched state showed an amorphous structure, and TEM observation revealed uniform in-situ precipitates of α-Fe nuclei smaller than 10 nm in the amorphous matrix, with concentrated and uniformly distributed nuclei. The saturation magnetic induction intensity B was measured. s The coercivity is 1.89 T, and the coercivity is H. c It is 7.5 A / m.

[0075] Comparative Example 1

[0076] This comparative example provides a high-Fe soft magnetic amorphous nanocrystalline alloy strip, which differs from Example 1 in that it does not use liquid nitrogen-assisted cooling, but its alloy composition, melting, and strip spinning process parameters are the same as those of Example 1.

[0077] The obtained alloy ribbon was characterized: XRD analysis in the quenched state showed an amorphous structure; such as Figure 3 As shown, the α-Fe crystal nuclei precipitated in the amorphous matrix are significantly larger, approximately 30 nm to 50 nm, and their distribution is uneven. Testing revealed that the saturation magnetic induction intensity of this comparative alloy strip is approximately 1.60 T, significantly inferior to that of Example 1. Therefore, liquid nitrogen-assisted cooling is crucial for achieving a copper roller surface temperature of -150°C to -196°C before the alloy melt contacts the roller, suppressing crystal nucleus coarsening, and ensuring uniform crystal nucleus precipitation. The absence of this feature will lead to coarse and uneven crystal nuclei and deterioration of magnetic properties.

[0078] Comparative Example 2

[0079] This comparative example provides a high-Fe soft magnetic amorphous nanocrystalline alloy strip, which differs from Example 1 in that: in the alloy composition, a=0.82, b=0.03, c=0.11, d=0.03, e=0.01, f=0.5; the melting and spinning process parameters are the same as in Example 1.

[0080] The obtained alloy strip was characterized as follows: due to the low Fe content, the viscosity and thermal conductivity of the melt changed, the thickness of the alloy melt on the surface of the copper roller was abnormal, the solidification heat transfer was unbalanced, the uniformity and size of α-Fe crystal nuclei were deteriorated, the crystal nuclei were coarse, mixed in size and unevenly distributed, and the magnetic properties were degraded. The results showed that Bs ~ 1.70 T and Hc ~ 14.5 A / m.

[0081] Therefore, the lower limit of Fe content of 0.83% plays a crucial role in maintaining the balance between melt properties and solidification heat transfer, and ensuring the uniform and fine precipitation of α-Fe crystal nuclei.

[0082] Comparative Example 3

[0083] This comparative example provides a high-Fe soft magnetic amorphous nanocrystalline alloy strip, which differs from Example 1 in that: in the alloy composition, a=0.83, b=0.04, c=0.09, d=0.03, e=0.01, f=0.5; the melting and spinning process parameters are the same as in Example 1.

[0084] The obtained alloy strip was characterized as follows: due to the high Si content, the melt viscosity increased, the thermal conductivity decreased, the melt spread was hindered, the spread thickness was too thick, the cooling rate was insufficient, the α-Fe crystal nuclei were coarsened and unevenly distributed, and the magnetic properties were deteriorated. The measured values ​​were Bs ~ 1.75 T and Hc ~ 17.4 A / m.

[0085] Therefore, the upper limit of Si content of 0.03% plays a crucial role in maintaining melt fluidity and thermal conductivity, ensuring cooling rate and crystal nucleus refinement.

[0086] Comparative Example 4

[0087] This comparative example provides a high-Fe soft magnetic amorphous nanocrystalline alloy strip, which differs from Example 1 in that: the surface roughness of the copper roller is 0.05μm; the alloy composition and other process parameters for melting and spinning are the same as in Example 1.

[0088] The obtained alloy strip was characterized as follows: due to the small surface roughness of the copper roller, the melt was difficult to form a continuous liquid film on the roller surface, resulting in discontinuous spreading and local accumulation, which led to uneven solidification and cooling, mixed α-Fe crystal nuclei, local coarsening, and deterioration of magnetic properties. The results showed that Bs ~ 1.72 T and Hc ~ 9.2 A / m.

[0089] Therefore, the limitation of the lower limit of the surface roughness of the copper roller to 0.1 μm plays a key role in ensuring the formation of a continuous liquid film and uniform cooling.

[0090] Comparative Example 5

[0091] This comparative example provides a high-Fe soft magnetic amorphous nanocrystalline alloy thin strip, which differs from Example 1 in that the surface roughness of the copper roller is 0.5μm, and the alloy composition and other process parameters for melting and spinning are the same as those in Example 1.

[0092] The obtained alloy strip was characterized as follows: due to the excessive surface roughness of the copper roller, the contact thermal resistance between the melt and the roller surface increased, the thermal conductivity decreased, the cooling rate was insufficient, the α-Fe crystal nuclei coarsened and became unevenly distributed, the coercivity increased, and the magnetic properties deteriorated. The results showed that Bs ~ 1.76 T and Hc ~ 16.3 A / m.

[0093] Therefore, limiting the surface roughness of the copper roller to 0.15 μm is crucial for ensuring efficient heat conduction and cooling rates and suppressing crystal nucleus coarsening.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-Fe soft magnetic amorphous nanocrystalline alloy thin strip, characterized in that, The alloy ribbon is made of (Fe) a Si b B c P d C e ) 100- f Cu f Composed of unavoidable impurities, where subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively, and satisfy the following: 0.83≤a≤0.86, 0.01≤b≤0.03, 0.08≤c≤0.11, 0.02≤d≤0.04, 0.01≤e≤0.02, 0.5≤f≤1, and a+b+c+d+e=1; The alloy strip, under quenched conditions, uniformly precipitates α-Fe crystal nuclei with a size of less than 10 nm in situ within an amorphous matrix.

2. The alloy strip according to claim 1, characterized in that, The alloy ribbon is made of (Fe) a Si 0.02 B c P 0.03 C 0.01 ) 99.5 Cu 0.5 It consists of unavoidable impurities, where 0.83≤a≤0.86, 0.08≤c≤0.11, and a+c=0.

94.

3. The alloy strip according to claim 1, characterized in that, The alloy strip has a saturation magnetic induction intensity Bs≥1.75T and a coercivity Hc≤15A / m.

4. A method for preparing the alloy thin strip according to any one of claims 1-3, characterized in that, include: Preparation of raw materials, based on (Fe a Si b B c P d C e ) 100-f Cu f The subscripts a, b, c, d, e, and f correspond to the atomic percentages of Fe, Si, B, P, C, and Cu, respectively. 0.83≤a≤0.86, 0.01≤b≤0.03, 0.08≤c≤0.11, 0.02≤d≤0.04, 0.01≤e≤0.02, and 0.5≤f≤1, and a+b+c+d+e=1. Choose either elemental or alloy raw materials. The raw materials are smelted; The alloy strip was prepared by a rapid cooling and spinning method.

5. The preparation method according to claim 4, characterized in that, In the rapid cooling and spinning method, the copper roller rotation speed is 40m / s-55m / s, and the cooling rate is 10. 5 K / s-10 6 K / s, copper roller surface roughness is 0.1μm-0.15μm, and alloy melt layup thickness is 10μm-20μm.

6. The preparation method according to claim 4, characterized in that, In the rapid cooling and spinning method, liquid nitrogen is used for assisted cooling so that the surface temperature of the copper roller is between -150°C and -196°C before the alloy melt comes into contact with the copper roller.

7. The preparation method according to claim 6, characterized in that, In the liquid nitrogen-assisted cooling, the liquid nitrogen injection flow rate is 0.5L / min-2.0L / min, and the distance between the liquid nitrogen nozzle and the surface of the copper roller is 0.2mm-1.0mm.

8. The preparation method according to claim 4, characterized in that, The melting process is carried out under vacuum, and the temperature is maintained at a temperature 150°C-200°C above the melting point of the alloy for at least 10 minutes.

9. The preparation method according to claim 4, characterized in that, The distance between the nozzle of the smelting furnace and the surface of the copper roller is 1mm-2mm.

10. The application of the alloy strip according to any one of claims 1-3 in high-frequency transformers, new energy vehicle drive motors, inductive components, magnetic sensors or electromagnetic shielding devices.

Citation Information

Patent Citations

  • Iron-based amorphous-nanocrystalline magnetically soft alloy and strip and preparation method thereof

    CN116313356A

  • Iron-based amorphous nanocrystalline soft magnetic alloy material as well as preparation method and application thereof

    CN120048609A